Size and shape regional differentiation during the development of the spine in the nine‐banded armadillo (Dasypus novemcinctus). Issue 6 (23rd November 2021) - Oliver, Jillian D.; Jones, Katrina E.; Pierce, Stephanie E.; Hautier, Lionel
Abstract: Xenarthrans (armadillos, anteaters, sloths, and their extinct relatives) are unique among mammals in displaying a distinctive specialization of the posterior trunk vertebrae—supernumerary vertebral xenarthrous articulations. This study seeks to understand how xenarthry develops through ontogeny and if it may be constrained to appear within pre‐existing vertebral regions. Using three‐dimensional geometric morphometrics on the neural arches of vertebrae, we explore phenotypic, allometric, and disparity patterns of the different axial morphotypes during the ontogeny of nine‐banded armadillos. Shape‐based regionalization analyses showed that the adult thoracolumbar column is divided into three regions according to the presence or absence of ribs and the presence or absence of xenarthrous articulations. A three‐region division was retrieved in almost all specimens through development, although younger stages (e.g., fetuses, neonates) have more region boundary variability. In size‐based regionalization analyses, thoracolumbar vertebrae are separated into two regions: a prediaphragmatic, prexenarthrous region, and a postdiaphragmatic xenarthrous region. We show that posterior thoracic vertebrae grow at a slower rate, while anterior thoracics and lumbars grow at a faster rate relatively, with rates decreasing anteroposteriorly in the former and increasing anteroposteriorly in the latter. We propose that different proportions between vertebrae and vertebral regions might result from differences in growth pattern and timing of ossification. Abstract : Ossification sequences in the mouse (Mus) and long‐nosed armadillo (Dasypus) vertebral elements as compared to regionalisation patterns (anterior thoracis in yellow, posterior thoracics in cyan, lumbars in blue) and vertebral growth. Vertebral neural arches are in red, vertebral centra are in blue, scapula and clavicle are in green, and ischium, ilium, and pubis are in orange. Highlights: Xenarthrans are unique vertebral xenarthrous articulations. We use three‐dimensional geometric morphometrics to explore phenotypic, allometric, and disparity patterns of vertebrae through development, and characterize vertebral regions of the xenarthran spine and how they develop.